Hubungan Risiko Pekerjaan Manual Handling Dengan Keluhan Low Back Pain Pada Pekerja Bagian Penuangan Cor Logam Di PT. Aneka Adhilogam Karya Ceper Klaten - WALUYO SAPUTRO, ADIN; , Tarwaka, PGDip.Sc.,M.Erg; , Dwi Astuti, SKM., M.Kes (2016)
Pouring metal casting in PT. Aneka Adhilogam Karya Ceper Klaten is still done by manual handling. This causes a risk of worker's low back pain. The purpose of this study was to analyze the correlation between the risks of manual handling working with low back pain among pouring metal casting workers. The method used is observational analytic with cross sectional approach. The population in this study is metal pouring cast workers totaling 19. The sampling technique used is total sampling, where the entire population is used as a sample. The univariate analysis showed that the percentage of manual handling working in the group of low risk (15,8%) was lower than in the group of middle risk (84,2%),while high risk was not found. the percentage of musculoskeletal disorders showed that low back pain in group of middle risk (26,3%) was lower than in the group of high risk (73,7%), while low risk and very high risk was not found. The data analysis used is the Spearman-Rho correlation with a significant level (α = 0.05). Based statistical result known that the value of p = 0.285 (> 0.05), it can be concluded that there is no correlation between the risk of manual handling work with low back pain among pouring metal casting workers in PT. Aneka Adhilogam Karya Ceper Klaten.